Analysis of sledge journeys - Reece, Alan (Polar Record, 1950)
The conditions of surface and weather in which sledge journeys are carried out, together with distances travelled and altitudes attained, are of great interest to anyone attempting to analyse and compare performances by various travellers. To obtain the necessary data the investigator must usually turn to the narrative of the journey concerned and extract the data himself, setting them out in some suitable form. Gordon Hayes adopts this procedure with many journeys in his Antarctica (London, 1928), and John Rymill gives an appendix, analysing the main journeys of the British Graham Land Expedition, 1934–37, in Southern Lights (London, 1938). Many other writers have made similar tables, but essential data always appear to be lacking, and there is no standard form to which such analyses can be reduced.